Le care : éthique féministe actuelle - Bourgault, Sophie; Perreault, Julie (Les éditions du remue-ménage, 2015)
Cet ouvrage présente une réflexion pluridisciplinaire sur l'éthique féministe du care. Élaborée par Carol Gilligan dans In a Different Voice en 1982, cette «éthique de la sollicitude» a été très prisée dans les années 1980. Plus récemment, nous assistons à l'émergence d'une enthousiaste seconde génération de théoricien.ne.s du care qui y voient un terreau fertile pour réfléchir aux oppressions liées à la division genrée du travail.Comment ce renouveau se traduit-il? Quels sont les enjeux éthiques, politiques et épistémologiques que permet de mettre en lumière cette approche? Le care équivaut-il essentiellement au travail de soin effectué en majorité par les femmes, ou comprend-il l'ensemble des services domestiques, affectifs et sexuels fournis dans un rapport d'interdépendance?L'originalité de ce premier ouvrage faisant le point sur la question au Québec tient entre autres à son souci constant de débarrasser le care du sentimentalisme qu'on lui a souvent reproché, et surtout, de le réinvestir de tout son potentiel critique et féministe.Avec des textes de Bettina Bergo, Agnès Berthelot-Raffard, Sophie Bourgault, Sophie Cloutier, Marjolaine Deschênes, Stéphanie Gaudet, Naïma Hamrouni, Mariko Konishi, Monique Lanoix, Patricia Paperman et Julie Perreault.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; discours dominant; division sexuelle du travail; inégalités; patriarcat; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé mentale; systèmes d'oppressions; thématiques; travail

Food and femininity - Cairns, Kate; Johnston, Josée (Bloomsbury Academic, 2015)
"Over the space of a few generations, women's relationship with food has changed dramatically. Yet – despite significant advances in gender equality – food and femininity remain closely connected in the public imagination as well as the emotional lives of women. While women encounter food-related pressures and pleasures as individuals, the social challenge to perform food femininities remains: as the nurturing mother, the talented home cook, the conscientious consumer, the svelte and health-savvy eater. In Food and Femininity, Kate Cairns and Josée Johnston explore these complex and often emotionally-charged tensions to demonstrate that food is essential to the understanding of femininity today. Drawing on extensive qualitative research in Toronto, they present the voices of over 100 food-oriented men and women from a range of race and class backgrounds. Their research reveals gendered expectations to purchase, prepare, and enjoy food within the context of time crunches, budget restrictions, political commitments, and the pressure to manage health and body weight. The book analyses how women navigate multiple aspects of foodwork for themselves and others, from planning meals, grocery shopping, and feeding children, to navigating conflicting preferences, nutritional and ethical advice, and the often-inequitable division of household labour. What emerges is a world in which women's choices continue to be closely scrutinized – a world where 'failing' at food is still perceived as a failure of femininity. A compelling rethink of contemporary femininity, this is an indispensable read for anyone interested in the sociology of food, gender studies and consumer culture."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; inégalités; ontario; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques; toronto; travail

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Care, environnement et éthique globale - Laugier, Sandra (Cahiers du Genre, 2015)
Cet article vise à mettre en évidence la puissance transformatrice des éthiques féministes du care pour les questions environnementales, et réciproquement, à montrer comment la question environnementale est le lieu présent de redéfinition des enjeux du care . En valorisant des caractéristiques morales identifiées comme féminines — l’attention, le souci des autres — l’éthique du care a contribué à placer la vulnérabilité au cœur de la morale, mais a aussi déplacé et élargi son champ. Ce que le care peut nous apprendre sur la question environnementale, c’est que le développement de nos sociétés riches occidentales n’a été possible que par leur dépendance par rapport à une nature, à des ressources — des animaux et des humains. La crise climatique est l’occasion de repenser l’idée de développement durable à partir du care .
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; care; cours; discipline; inégalités; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; écoféminisme